Efficacy of Pond Ash as a Cover Material in Single and Dual Capillary Barriers - Srikanth C.S.S.U.; Ramaiah B.J.; Murali Krishna A.; Vanapalli Sai K. (E3S Web of Conferences, 2023)
In this paper, numerical study results that highlight the capability of using pond ash as a cover material in covers with capillary barrier effects are succinctly summarized. A model was exclusively developed and calibrated using commercial software SEEP/W for this study. After calibration, the efficiency of pond ash as a coarse-grained layer (CGL), fine-grained layer (FGL), unsaturated drainage layer (UDL), and seepage control layer (SCL) was investigated using various combinations. The CCBE made of pond ash obtained from the output and input points of an ash pond as alternate fine- and coarse-grained layers were observed to perform well. The performance of pond ash as UDL and SCL was also observed to be good. The approach presented in this study is valuable in assessing likely slope failures of coal ash storage facilities that may be triggered by rainfall events. The study aids in significantly reducing rainfall infiltration, improving the overall stability of the slopes, and promoting sustainability by utilising the concept of “waste covering waste”. The approaches used in this study can be extended in the rational design of slopes to address the future challenges anticipated with unprecedent rainfall events and its negative impacts associated with climate change effects.